2004
DOI: 10.1021/ja036352y
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of CO on Gold Supported Catalysts Prepared by Laser Vaporization: Direct Evidence of Support Contribution

Abstract: Gamma-Al2O3, ZrO2, and TiO2 gold supported model catalysts have been synthesized by laser vaporization. Structural characterization using Transmission Electron Microscopy and X-ray Photoelectron Spectroscopy experiments have shown that the gold clusters deposited on the different supports have similar distribution of size centered around 3 nm and are in the metallic state. However, X-ray photoemission measurements also indicate lower binding energies than the usual Au 4f(7/2) at 84.0 eV for both alumina and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
270
3
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(306 citation statements)
references
References 47 publications
30
270
3
3
Order By: Relevance
“…2 and 3, a, after catalytic reaction a further decrease of the Au 4f BE in the used catalyst occurred as compared with the fresh one, with the total negative shift with respect to the bulk Au amounting to 0.45  0.05 eV for DP1 and 0.41  0.03 eV for DP2. This observation is in agreement with other works [6,7,18] reporting a similar shift of the Au 4f spectrum toward lower binding energies for Au/TiO 2 catalysts used in the CO oxidation reaction. The additional negative shift of the Au 4f line in the used catalyst may result a b c Fig.…”
Section: supporting
confidence: 93%
See 2 more Smart Citations
“…2 and 3, a, after catalytic reaction a further decrease of the Au 4f BE in the used catalyst occurred as compared with the fresh one, with the total negative shift with respect to the bulk Au amounting to 0.45  0.05 eV for DP1 and 0.41  0.03 eV for DP2. This observation is in agreement with other works [6,7,18] reporting a similar shift of the Au 4f spectrum toward lower binding energies for Au/TiO 2 catalysts used in the CO oxidation reaction. The additional negative shift of the Au 4f line in the used catalyst may result a b c Fig.…”
Section: supporting
confidence: 93%
“…The data on the chemical and electronic state of gold nanoparticles in different catalysts used in the CO oxidation as determined by the Au 4f binding energy are rather contradictory, although they clearly indicate that formation and modification of the particles' electronic state strongly depend on the nature of support. For the Au/TiO 2 system, in which gold was in a metallic state, the reaction of CO oxidation was observed to cause an appreciable shift of the Au 0 4f peak to lower binding energies as compared to the fresh catalyst [6,7]. A similar negative shift of the Au 4f and Au 4d lines was also reported for an Au/Al 2 O 3 catalyst used in the CO oxidation [8].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…7 The attention to these catalysts has not diminished, as is evidenced by the number of reports published by many groups over the last year. [8][9][10][11][12][13][14][15][16][17][18][19][20] Despite all of this attention, the mode of operation of these catalysts is still under discussion, especially for the epoxidation of propene. Both gold and titania seem to be a necessity for a catalyst to be able to epoxidize propene.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the catalyst preparation technique has a significant impact on the performance of GNPs catalysts, and hence, research has focussed on the use of various techniques to prepare supported GNPs such as coprecipitation [41], chemical vapour deposition [50], impregnation [51], grafting [52], photo-deposition [53], physical mixing [54], low-energy cluster beam deposition [55], adsorption of Au colloids on metal oxides [56] and ion-exchange [57]. In general, GNP catalysts prepared with the deposition-precipitation technique exhibited the highest activity [41].…”
Section: Low-temperature Oxidation Of Comentioning
confidence: 99%